Object localization using stereo sensors for adept SCARA robot - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Nagaran, R.; Sazali, Yaacob (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org